Early ontogeny of the olfactory organ in a basal actinopterygian fish: Polypterus - Zeiske, Eckart (2009)
The present study employed light and electron microscopic methods to investigate the ontogenetic origin of the olfactory organ in bichirs (Cladistia: Polypteridae) and explore its evolution among osteichthyans. In former studies we demonstrated that in teleosts a subepidermal layer gives rise to the olfactory placode which in turn builds all types of olfactory cells (basal, receptor, supporting, ciliated non-sensory cells). In contrast, the olfactory placodes in sturgeons (Chondrostei: Acipenseridae) as well as in the clawed frog Xenopus laevis (Anura: Pipidae) originate from two different layers. Receptor neurons derive from cells of the subepidermal (sensory) layer and supporting cells from epidermal cells. As sturgeons and amphibians in some characters show a more primitive condition than teleosts, we extended our study to Polypterus to allow for an approach at the basic osteichthyan pattern. In Polypterus, an internal lumen occurs in early ontogenetic stages surrounded by the epithelium of the olfactory placode. Two different populations of supporting cells follow one another: a primary population derives from the subepidermal layer. Later supporting cells develop from epidermal cells by transdifferentiation. The primary opening of the internal lumen to the exterior develops by invagination from the epidermal surface and simultaneously by a counter-directed process of cell dissociation and fragmentation inside the olfactory placode. Our results indicate the following features to be plesiomorphic actinopterygian character states: The primary olfactory pit (prospective olfactory cavity) is formed by invagination of the epidermal and the subepidermal layer (as in Acipenser and Xenopus). The incurrent and excurrent nostrils derive from a single primary opening which elongates and is then separated by an epidermal bridge into the two external openings (as in Acipenser and many teleosts). The olfactory epithelium derives from an epidermal and a subepidermal layer (as in Acipenser and Xenopus). Apomorphic (derived actinopterygian) features are: (1) an internal lumen as primordium of the future olfactory chamber; (2) a subepidermal layer gives rise to the olfactory epithelium and its constituents (Polypterus and teleosts). As to the origin of the olfactory supporting cells in Polypterus we assume a combination of plesiomorphic and apomorphic characters. We conclude that Acipenser and Xenopus exhibit the most widely distributed features among basal osteognathostomes and thus ancestral character states in the development of the olfactory organs.